Production Of Lecithin As An Emulsifier From Vegetable Oil Using Water Degumming Process - Alwani Hamad; Noni Indriani; Anwar Ma'ruf (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2022)
Lecithin is a phospholipid that has amphiphilic properties resulted polar and non-polar regions, thus it is very effective to be food emulsifier. However, commercial lecithin derived from animal organs such as pig brain, that it is clearly haram. Today, commercial vegetable lecithin derived from soybean oil only. Therefore, lecithin production from other vegetable oils can be made Halal food. In this study, it determined production of lecithin from vegetable oils (coconut oil, palm oil, corn oil and soybean oil) using water degumming process. Vegetable oil is heated up to 70 ° C and added 3% of soft water and then stirred for an hour. To separate the gum, it is used centrifuge at 5000 rpm for 20 minutes. The results showed that only gum from corn oil that can be potentially produce crude lecithin as an emulsifier, resulted gum dry yield (0.11%) and acetone insoluble (AI) 62.75%. This result has significantly the same with soybean lecithin as a control. Unfortunately, it has water content of 6.14% that need further improvement.